Project management training for “Indy Soulart Fiberglass” to increase productivity - Moh. Jufri; Ali Saifullah; Ary Dwi Astuti; Muh. Alfin Masykur Muharram; Arista Dwi Setya Budi; Muhammad Mawlana; Muhammad Ramdani; Ivan Dwi Oktavianto; Erwin L. Rimban (Peneliti Teknologi Teknik Indonesia, 2021)
Business development depends on good management and extensive promotion to customers. In addition, courteous prompt response from customer service can be an advantage to influence customer decisions to order products. This community service program uses interview and observation methods to solve problems in this small fiberglass industry. Interviews and observations were conducted to analyze the situation and determine the solution to the problem. Training for the creative industry of Indy Soulart Fiberglass helps them carry out extensive promotions to reach their customers and have good management. Creating a built web page introduces their profile in product processing. Professionalism and punctuality are also displayed on the website to gain customer trust. In addition, customers are given information about contact persons on the web page to make it easier for them when they want to place an order. A project management system is built to manage orders. Business owners can track product creation progress from design to product ready to ship. This system helps the owner to monitor the running of the business. Thus, the business can gradually operate effectively and efficiently. The improved business situation at Indy Soulart Fiberglass shows that providing information on the internet and owner supervision is necessary to keep the business growing. Complete information shared with customers can influence the customer's decision to order the product. Meanwhile, the project management system helps the owner control the product manufacturing process.